Multi-stimuli responsive poly(amidoamine) dendrimers with peripheral N-dialkylaminoethyl carbamate moieties. Issue 5 (10th January 2019) - Tong, Qi-Song; Xu, Wei; Huang, Qiu-Yue; Zhang, Ya-Ru; Shi, Xiao-Xiao; Huang, Hua; Li, Hong-Jun; Du, Jin-Zhi; Wang, Jun
Abstract : A novel type of multi-stimuli responsive dendrimer with thermo-, pH-, and CO2 -responsiveness was developed through facile modification of polyamidoamine dendrimers with various N -dialkylaminoethyl carbamate moieties. Abstract : A novel type of multi-stimuli responsive dendrimer with thermo-, pH-, and CO2 -responsiveness was developed through facile modification of polyamidoamine dendrimers (PAMAM) with various N -dialkylaminoethyl carbamate moieties. A series of modified PAMAM dendrimers with a well controlled structure were obtained and characterized by 1 H NMR. The aqueous solutions of these dendrimers showed a lower critical solution temperature (LCST)-type thermoresponse, and their cloud point temperature ( T cp ) was determined by turbidity measurements. T cp was tunable from 8 to 70 °C, depending on the hydrophobicity and substitution number of the terminal N -dialkylaminoethyl groups, PAMAM generation, pH values, and salt concentrations. Additionally, the solubility of the resultant dendrimers could be reversibly modulated by alternately bubbling CO2 and argon. Our study offers a simple but effective approach to making new multi-stimuli responsive dendrimers for potential smart material applications.